PSO localization algorithm for WSN nodes based on modifying average hop distances - Yan-hang ZHAO; Zhi-hong QIAN; Xiao-hang SHANG; Chao CHENG (Tongxin xuebao)
Regarding the relatively big errors with running the DV-hop localization algorithm in a network topology scenario,with which nodes randomly distributes,a particle swarm optimization localization algorithm for WSN nodes based on modifying average hop distance was proposed.changing the structure of data packets sent by anchor nodes with broadcasting,weighting the average hop distance error of reference anchor nodes to modify the average hop distance,and using an improved particle swarm algorithm to optimize iteration process for localization,thus,WPDV-Hop localization algorithm improvements were carried out.The simulation results indicate that the localization accuracy and the stability of the WPDV-Hop localization algorithm are significantly improved compared with the original algorithm.